Nerve sheath myxoma of the dorsal paravertebral space - Malkoç, Melih; Örmeci?, Tu?rul; Keskinbora, Mert; Yılmaz, Adem; Korkmaz, Özgür; Besleyici Tanık, Canan (Elsevier, 2014)
Introduction Nerve sheath myxomas (NSM) are rare benign soft tissue tumors. The dorsal paravertebral placed NMS diagnosis can be difficult.PRESENTATION OF CASE This article presents clinical, radiological findings and treatment of the NSM of the dorsal paravertebral space in a 32-year-old man presented with a right shoulder and back pain for 4 years.DISCUSSION NSM is a rare and benign tumor and that most often occurs in the skin of the head, neck or upper limbs of younger patients. Rare locations such as intracranial, spinal canal, trunk, lower limb and oral cavity were also reported. The appropriate treatment of NSM is surgical excision. Diagnosis is difficult in an uncommon presentation.CONCLUSION Although the most presented case of NMS are dermal tumors, it may also be found extremely rare locations. We conclude that, the definitive treatment of NSM is surgical excision with safe margins even when it is possible.
Keywords: Myxoma; Nerve Sheath Tumor; Neurothekeoma; Paravertebral Space